Patient Reported Outcome Measures Assessing Health-Related Quality Of Life in Dupuytren´S Disease: A Systematic Review - Gómez Herrero, Diego; Sanjuan-Cerveró, Rafael; Vazquez-Ferreiro, Pedro; Carrera-Hueso, Francisco Javier; Sáez-Belló, Marina; Vila-Miralles, Rocio; García-Jiménez, Emilio (International Journal of Innovative Research in Medical Science, 2020)
Objective: The objective of this study is to carry out a systematic review of the outcome measures reported by the patient that are used to measure the quality of life of patients with Dupuytren´s disease (DD), assessing their relevance and effectiveness. Methods: A systematic literature search was carried out in the PubMed®, Web of Sciencie®, SciELO®, EMBASE®, Google Scholar® and Cochrane® databases. We searched for peer-reviewed articles evaluating health related quality of life (HR-QoL) in patients with DD diagnosed and/or treated until April 1, 2017, for English or Spanish language. The following keywords were used: “Dupuytren´s disease (MeSH)” AND “health related quality of life (MeSH)”. The documents were eligible for inclusion if they described data on the HR-QoL domains in relation to diagnosis or treatment of DD after a revision process by two independent authors. The checklist (STROBE) was used to evaluate the quality of the works. Results: From 352 identified articles were finally selected 26 studies in the systematic review, mostly European. A total of nine outcomes measures specifically reported by the patient were identified: DASH (used in 13 of the 26 selected studies), Quick-DASH (8/26), MHQ (7/26), briefMHQ (1/26), URAM (4/26), POS-HAND/ARM (1/26), SDSS (1/26), DDSP (1/26) and CHFS (1/26) questionnaires. We analyze their quantitative results to evaluate the effectiveness and evaluate the methodological quality of the studies on the measurement properties of the results reported by patients related to health. Conclusion: More work is urgently needed in these areas before we can reach a consensus on which instrument is the best to assess functional deterioration and improvement in patients with DD.